2020
DOI: 10.1080/02670836.2020.1753933
|View full text |Cite
|
Sign up to set email alerts
|

Improved elevated temperature mechanical properties of graphene-reinforced pure aluminium matrix composites

Abstract: In this study, graphene nanoplatelets (0.25 and 0.5 wt-%) reinforced aluminium matrix composites were synthesised. Microstructures of composites were investigated by X-ray diffraction, scanning electron microscope and transmission electron microscope. Hardness was measured according to the Vickers test method. Tensile tests were performed at both room (25°C) and elevated temperatures (150°C and 250°C). Results showed that hardness was improved with direct addition of graphene. Microstructure of composites was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 42 publications
0
10
0
2
Order By: Relevance
“…Thus, the composite materials possess higher yield and compressive strengths than those recorded with the AZ91 matrix. Many researchers [ 11 , 33 , 34 ] reported that the introduction of carbon-based reinforcements result in an improvement in the strength of the produced metal matrix composites. This positive effect on the strength may be due to the dislocation movement effected by carbon-based reinforcement, which results in the load transfer effect mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the composite materials possess higher yield and compressive strengths than those recorded with the AZ91 matrix. Many researchers [ 11 , 33 , 34 ] reported that the introduction of carbon-based reinforcements result in an improvement in the strength of the produced metal matrix composites. This positive effect on the strength may be due to the dislocation movement effected by carbon-based reinforcement, which results in the load transfer effect mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Nessa figura a microdureza encontra-se expressa em termos do ganho percentual relativo (comparação com o alumínio não reforçado), permitindo assim uma melhor comparação entre os diferentes trabalhos. A seleção dos trabalhos utilizados nesta comparação foi baseada na semelhança em termos de metodologia de processamento (metalurgia do pó/moagem de alta energia) (ALRASHEEDI, 2016;BAIG et al, 2018;BARTOLUCCI et al, 2011;DASARI et al, 2018;ELGHAZALY;ANIS;SALEM, 2017;KHAN et al, 2017;LATIEF et al, 2011;XIONG, 2017a;LI et al, 2018a;LIU et al, 2016a;PÉREZ-BUSTAMANTE et al, 2014;RAJ et al, 2020;SUN et al, 2017;SYED NASIMUL ALAMN, 2016;TURAN;AYDIN, 2020;WANG et al, 2019. Em função de não haver outros trabalhos na literatura até o momento que apresentem resultados de microdureza para NCMAs reforçados com rGO quimicamente reduzido, foi incluído nessa comparação os resultados de microdureza para o NCMA-rGO termicamente reduzido e NCMA reforçado com outros materiais grafênicos (GNPs ou GNS), como detalhado na legenda da Figura 6. Verifica-se nesta Figura, em função…”
Section: Microdureza Dos Ncmasunclassified
“…Estas podem ser divididas em duas grandes categorias: (i) as abordagens bottom-up (do inglês, de baixo para cima), que incluem o crescimento epitaxial por decomposição térmica de carbeto de silício e a deposição química em fase vapor de grafenos em superfícies metálicas; e (ii) as abordagens topdown (do inglês, de cima para baixo), que incluem os métodos de esfoliação mecânica(ANTISARI et al, 2006;PARK;RUOFF, 2009;ZHAO et al, 2010), a esfoliação química do The Great World of Nanotechnology Vol II Chapter 14 186 grafite em líquidos (PARK; Figura 2 -Modelo esquemático para a estrutura química de uma única camada de óxido de grafeno (a) e do óxido de grafeno reduzido (b).e (iii) a degradação do ordenamento cristalino das fases durante o processamento. Para superar tais dificuldades, muitas estratégias têm sido desenvolvidas nos últimos anos (KHANNA; KUMAR; BANSAL, 2021), inclusive a avaliação de diferentes métodos de processamento, como a metalurgia líquida, a metalurgia do pó, a liga mecânica por 2016; TURAN;AYDIN, 2020;WANG et al, 2019).Neste trabalho, a metalúrgica do pó foi utilizada na obtenção de um nanocompósito de matriz de alumínio reforçado com rGO (NCMA-rGO). O efeito da concentração de rGO na microdureza do nanocompósito foi avaliado.The Great World of Nanotechnology Vol II…”
unclassified
“…The presence of internal stresses is particularly important in the case of ceramics subject to fracture toughness [ 23 ].Tensile residual stress leads to the formation of micro-cracks, which has a negative influence on fatigue life. On the other hand, comprehensive residual stress develops the strength and fracture toughness of materials [ 24 , 25 , 26 , 27 ]. Ceramic matrix composites are expected in the presence of tensile and compressive residual stresses due to the thermal expansion mismatch between the different phases and the thermal expansion anisotropy of different phases during the cooling step [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%